Different techniques of vessel reconstruction during kidney transplantation - Tomić, Aleksandar; Milović, Novak; Marjanović, Ivan; Bjelanović, Zoran; Leković, Ivan; Micković, Saša; Stamenković, Dušica (Vojnosanitetski pregled, 2015)
Background/Aim. Multiple renal arteries (MRAs) represent a surgical challenge by the difficulty in performing anastomoses, bleeding and stenosis. MRAs should be preserved and special attention should be paid to accessory polar arteries. All renal arteries (RAs) must be reconstructed and prepared for safe anastomosis. The paper decribed the different techniques of vessel reconstruction during kidney transplantation including important steps within recovery of organs, preparation and implantation. Methods. In a 16-year period (1996–2012) of kidney transplantation in the Military Medical Academy, Belgrade, a total of 310 living donors and 44 human cadaver kidney transplantations were performed, of which 28 (8%) kidneys had two or more RAs. Results. All the transplanted kidneys had immediate function. We repaired 20 cases of donor kidneys with 2 arteries, 4 cases with three RAs, one case with 4 RAs, one case with 4 RAs and renal vein reconstruction, one case with 3 arteries and additional polytetrafluoroethylene (PTFE) graft reconstruction, one case with transected renal artery and reconstruction with 5 cm long deceased donor external iliac artery. There were no major complications and graft failure. At a minimum of 1-year follow-up, all the patients showed normal renal function. Conclusion. Donor kidney transplantation on a contralateral side and “end-to-end” anastomosis of the renal artery to the internal iliac artery (IIA) is our standard procedure with satisfactory results. Renal artery reconstruction and anastomosis with IIA is a safe and highly efficient procedure and kidneys with MRAs are not contraindicated for transplantation. A surgical team should be fully competent to remove cadaveric abdominal organs to avoid accidental injuries of organs vessels.